Emission and economic performance assessment of a solid oxide fuel cell micro-combined heat and power system in a domestic building - Elmer, Theo; Worall, Mark; Wu, Shenyi; Riffat, Saffa (Elsevier, 2015)
Combined heat and power (CHP) is a promising technological configuration for reducing energy consumption and increasing energy security in the domestic built environment. Fuel cells, on account of their: high electrical efficiency, low emissions and useful heat output have been identified as a key technological option for improving both building energy efficiency and reducing emissions in domestic CHP applications. The work presented in this paper builds upon results currently reported in the literature of fuel cells operating in domestic building applications, with an emission and economic performance assessment of a real, commercially available SOFC mCHP system operating in a real building; under a UK context.